2020
DOI: 10.1080/21645515.2020.1775455
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pneumococcal conjugate vaccines on otitis media from 2005 to 2013 in children aged ≤5 years: a retrospective cohort study in two Swedish regions

Abstract: Seven-valent pneumococcal conjugate vaccine (PCV7) was introduced to Sweden in 2009 and replaced by pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) or 13-valent PCV (PCV13) from late 2009. A retrospective cohort study assessed the impact of PCVs on otitis media/acute otitis media (OM) in children aged ≤5 years (NCT02742753) living in Skåne (PCV7 then PHiD-CV) or Västra Götalandsregionen (PCV7 then PCV13) between 2005 and 2013 using linked regional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Antibiotic prescribing for OM showed strong annual seasonality and significant levels of autocorrelation in all ages and in each vaccine era (Figure S1), which mirrored OM incidence rates. 18 Before the introduction of PCV, antibiotic prescribing rates for OM in children aged ≤5 years were higher in Skåne than in VGR, particularly among children aged 1 year (Figure S1), also mirroring trends observed in OM incidence rates. 18 The interrupted time-series showed a decrease in antibiotic prescribing (events per 100,000 person-years) between the pre-PCV period and the PHiD-CV period that was statistically significant in 1 year-olds (−697, 95% CI: −1138; −255), 2 yearolds (−369, 95% CI: −655; −83), and ≤5 years (−314, 95% CI: −616; −13) (Table S3).…”
Section: Antibiotic Prescriptions For Ommentioning
confidence: 63%
See 3 more Smart Citations
“…Antibiotic prescribing for OM showed strong annual seasonality and significant levels of autocorrelation in all ages and in each vaccine era (Figure S1), which mirrored OM incidence rates. 18 Before the introduction of PCV, antibiotic prescribing rates for OM in children aged ≤5 years were higher in Skåne than in VGR, particularly among children aged 1 year (Figure S1), also mirroring trends observed in OM incidence rates. 18 The interrupted time-series showed a decrease in antibiotic prescribing (events per 100,000 person-years) between the pre-PCV period and the PHiD-CV period that was statistically significant in 1 year-olds (−697, 95% CI: −1138; −255), 2 yearolds (−369, 95% CI: −655; −83), and ≤5 years (−314, 95% CI: −616; −13) (Table S3).…”
Section: Antibiotic Prescriptions For Ommentioning
confidence: 63%
“…18 Before the introduction of PCV, antibiotic prescribing rates for OM in children aged ≤5 years were higher in Skåne than in VGR, particularly among children aged 1 year (Figure S1), also mirroring trends observed in OM incidence rates. 18 The interrupted time-series showed a decrease in antibiotic prescribing (events per 100,000 person-years) between the pre-PCV period and the PHiD-CV period that was statistically significant in 1 year-olds (−697, 95% CI: −1138; −255), 2 yearolds (−369, 95% CI: −655; −83), and ≤5 years (−314, 95% CI: −616; −13) (Table S3). In VGR, statistically significant decreases were observed in all age years, with an overall change in slope of −356 (95% CI: −531; −181) from the pre-PCV to the PCV13 period (Table S3).…”
Section: Antibiotic Prescriptions For Ommentioning
confidence: 63%
See 2 more Smart Citations
“…Results of a study in Sweden showed that pneumococcal conjugate vaccines reduce the incidence of otitis media up to 26% and delay the first episode of otitis media in infants and young children [ 15 ]. This could be due to the reduced nasopharyngeal colonization of bacteria by PCVs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%